Comparison Between The Experimentally and Numerically Modeled and Simulated Kinetic Parameters Corresponding to Michaelis-Menten Equation for NADH Sensors Based on Polymeric Phenothiazine Modified Electrodes - LIGIA UNGURESAN*, MIHAELA; MARIA GLIGOR†, DELIA (Asian Journal of Chemistry, 2009)
The paper presents a comparison between the experimentally andnumerical modeled and simulated kinetic parameters (Michaelis-Mentenconstant, KM and Imax) obtained by fitting the Michaelis-Menten equation,for NADH amperometric measurements at electrodes modified withpolymeric phenothiazines. The modified electrodes were obtained bytwo different approaches: (i) adsorption of the poly-phenothiazine formaldehyde(PPF) on graphite electrodes (G/PPF) and (ii) electro polymerizationof bis-phenothiazin-3-yl-methane (BPhM) on glassy carbon electrodes(GC/poly-BPhM). It was obtained a good correlation of the simulatedkinetic parameters with the experimental values. GC/poly-BPhM electrodespresent a higher sensitivity for NADH detection than G/PPF electrodes,at an applied potential of +200 mV vs. SCE and +50 mV vs. SCE,respectively.